Fluid accumulation during acute kidney injury in the intensive care unit. Issue 6 (7th March 2018) - Berthelsen, R. E.; Perner, A.; Jensen, A. K.; Jensen, J.‐U.; Bestle, M. H.
Abstract : Introduction: Fluid therapy is a ubiquitous intervention in patients admitted to the intensive care unit, but positive fluid balance may be associated with poor outcomes and particular in patients with acute kidney injury. Studies describing this have defined fluid overload either at specific time points or considered patients with a positive mean daily fluid balance as fluid overloaded. We wished to detail this further and performed joint model analyses of the association between daily fluid balance and outcome represented by mortality and renal recovery in patients admitted with acute kidney injury. Method: We did a retrospective cohort study of patients admitted to the intensive care unit with acute kidney injury during a 2‐year observation period. We used serum creatinine measurements to identify patients with acute kidney injury and collected sequential daily fluid balance during the first 5 days of admission to the intensive care unit. We used joint modelling techniques to correlate the development of fluid overload with survival and renal recovery adjusted for age, gender and disease severity. Results: The cohort contained 863 patients with acute kidney injury of whom 460 (53%) and 254 (29%) developed 5% and 10% fluid overload, respectively. We found that both 5% and 10% fluid overload was correlated with reduced survival and renal recovery. Conclusion: Joint model analyses of fluid accumulation in patients admitted to the intensive care unit with acute kidney injury confirm that even a modest degree of fluid overload (5%) may be negatively associated with both survival and renal recovery.